Electronic properties calculation for silicon using castep and molc toy software (single-electron transistor) - 342763 Noraishah Ramli; Ahmad Radzi Mat Isa, supervisor; Fakulti Sains (2007)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2007